BIG DATA TECHNOLOGIES: CONCEPT, PURPOSE, AND APPLICATIONS - А. О. Utepbergenov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The purpose of the article is to identify and analyze opportunities to optimize human resource management in the selected companies using digital technologies, in particular, to retain valuable employees and develop professional and other competencies, as well as to develop recommendations to similar companies to implement and develop BIG DATA technologies in talent management in today’s economy.